Implementation of the Arabic Language Habituation Program in Improving Academic Achievement of Students in SMP Muhammadiyah 9 Tanggulangin Boarding School: Implementasi Program Pembiasaan Bahasa Arab dalam Meningkatkan Prestasi Akademik Peserta Didik di SMP Muhammadiyah 9 Boarding School Tanggulangin - Zamzami, Rifa’atus Shoolihah; Nurdyansyah, Nurdyansyah; Churrahman, Taufiq (Proceedings of The ICECRS, 2020)
This research is intended to study the Arabic Language Implementation Program in improving Academic Achievement of Tanggulangin 9 Muhammadiyah Middle School Students. This type of research is field research (field research) by discussing descriptive qualitative analysis. Data collection is done by interviewing, collecting and collecting, while data analysis uses analytical techniques namely data reduction, data presentation, and conclusion collection. The results obtained in this study are the Arabic Habituation Program which contains writings of mufrodat, muhadasah and muhadharah which are very supportive of the Academic Achievement of Muhammadiyah 9 Middle School Students at Tanggulangin Islamic Boarding School. This is evidenced from the results that have been obtained by SMP Muhammadiyah 9 Tanggulangin related to Arabic. Constraints that support the pelasa program are habits and facilities that are less supportive.